Nature inside : plants and flowers in the modern interior - Sparke, Penny (New Haven : Yale University Press, 2020)
"From ferns in 19th-century British parlors to contemporary "living walls" in commercial spaces, plants and flowers have long been incorporated into the design of public and private spaces. Spanning two centuries, Nature Inside explores the history and popularity of indoor plants, revealing the close relationship between architecture, interior design, and nature. Studying the international modern interior through the lens of plants in the human environment, author Penny Sparke attributes a degree of the interest in indoor plants to urbanization, and, more recently, the climate crisis, which serve as ongoing reminders that people must maintain a connection to, and respect for, the natural world. While architectural and interior design styles have evolved alongside the popularity of various plant species, the human need to bring nature indoors has remained constant."--
Taming the jungle -- The jungle in the parlour -- The parlour outside -- Natural modernism -- The garden inside: the Villa Tugendhat, Brno -- Living in the garden: California modernism -- Natural late modernism -- The living room in the city: the Hyatt Regency Hotel, Atlanta -- The benefits of nature inside -- Greening the interior.
boek